Construction and Validation of Novel Nomograms for Predicting Prognosis of Pancreatic Ductal Adenocarcinoma After Surgery According to Different Primary Cancer Locations - Li, Ge; Liao, Cheng-Yu; Chen, Jiang-Zhi; Huang, Long; Yang, Can; Tian, Yi-Feng; Wang, Yi-Ting; Du, Qiang; Zhan, Qian; Chen, Yan-Ling; Chen, Shi (Frontiers in Oncology, 2021)
Background/Aims: Pancreatic ductal adenocarcinoma (PDAC) can occur in different parts of the pancreas. This study aimed to identify clinicopathological characteristics independently correlated with the prognosis of PDAC of the pancreatic head/uncinate (PHC) or body-tail (PBTC), and to develop novel nomograms for predicting cancer-specific survival (CSS) according to different primary cancer locations. Methods: 1160 PDAC patients were retrospectively enrolled and assigned to training and test sets with each set divided into PHC and PBTC groups. Comparative analysis of clinicopathologic characteristics, survival analysis, and multivariate analysis were performed. Independent factors were identified and used for constructing nomograms. The performance of the nomograms was validated in the test set. Results: Primary tumor location was an independent risk factor for prognosis of PDAC after surgery. Specially, gender, fasting blood glucose, and preoperative cancer antigen 19-9 were significantly associated with prognosis of PHC, whereas age, body mass index, and lymph nodes were significantly correlated with the prognosis of PBTC. A significant difference in prognosis was found between PHC and PBTC in stage Ia and stage III. Three nomograms were established for predicting the prognosis for PDAC, PHC, and PBTC. Notably, these nomograms were calibrated well (c-indexes of 0.690 for PDAC, 0.669 for PHC, and 0.704 for PBTC), presented high accuracy and reliability, and achieved clinical validity. Conclusions: PHC and PBTC share the different clinical-pathological characteristics and survival.The nomograms show good performance for predicting prognosis in PHC, and PBTC. Therefore, these nomograms hold potential as novel approaches for predicting survival of PHC and PBTC patients after surgery.